1984
DOI: 10.1111/j.1365-2885.1984.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of theophylline in horses

Abstract: The pharmacokinetics and bioavailability of theophylline in horses were investigated following both intravenous and intragastric administration of aminophylline solutions at doses corresponding to 15 and 10 mg/kg theophylline base. A rapid distributive phase with a half-life of approximately 15-30 min was followed by a slower elimination half-life averaging 15-17 h. The apparent volume of distribution averaged 850-900 ml/kg. Theophylline, administered as aminophylline solution, was both rapidly and completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
6
12
1
Order By: Relevance
“…This value agrees with some previous reports (Errecalde et al, 1984;Ingvast Larson et al, 1985), although a faster elimination rate was reported by Short et al (1986).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This value agrees with some previous reports (Errecalde et al, 1984;Ingvast Larson et al, 1985), although a faster elimination rate was reported by Short et al (1986).…”
Section: Discussionsupporting
confidence: 94%
“…Such variation has been reported in previous studies (Ingvast Larson et al, 1985). The first distribution phase (a) was rapid, being faster than that in some previous reports (Errecalde et aL, 1984;Ingvast Larson et al, 1985) but agreeing with that reported by Ayres et al (1985). This difference may have been caused by the different models used in the analysis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations